2019
DOI: 10.1007/jhep12(2019)146
|View full text |Cite
|
Sign up to set email alerts
|

Integrable sigma models and 2-loop RG flow

Abstract: Following arXiv:1907.04737, we continue our investigation of the relation between the renormalizability (with finitely many couplings) and integrability in 2d σ-models. We focus on the "λ-model," an integrable model associated to a group or symmetric space and containing as special limits a (gauged) WZW model and an "interpolating model" for non-abelian duality. The parameters are the WZ level k and the coupling λ, and the fields are g, valued in a group G, and a 2d vector A ± in the corresponding algebra. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 93 publications
(190 reference statements)
5
64
0
Order By: Relevance
“…We have also seen that the σ-model (2.1) is renormalizable without the need to correct the target space geometry, for the case of an isotropic coupling matrix and of an anisotropic coupling for the SU(2) case. For an isotropic coupling matrix this fact was also observed in [28].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We have also seen that the σ-model (2.1) is renormalizable without the need to correct the target space geometry, for the case of an isotropic coupling matrix and of an anisotropic coupling for the SU(2) case. For an isotropic coupling matrix this fact was also observed in [28].…”
Section: Discussionsupporting
confidence: 64%
“…September 2019) [26] and at the 10 th Crete regional meeting in String Theory (Kolymbari, Greece, 15-22 September 2019) [27]. Towards the completion of the present work, the work of [28] appeared where similar issues concerning the two-loop β-function in λ-deformed models, are discussed.…”
Section: Note Addedmentioning
confidence: 99%
“…With the structure constants related by (4.8), we can derive the following three equations 2 Here EA I has the natural weight 3 5 .…”
Section: The Frame Fields and Embedding Tensormentioning
confidence: 99%
“…Non-Abelian T-duality [1] is a proposed dualisation of closed-string non-linear sigma-models (NLSM) whose target space admits the action of non-Abelian isometry group. Whilst the status of Non-Abelian T-duality in terms of the string genus expansion remains unclear, recent evidence [2] at two-loops provides confidence that the duality could remain robust to quantum (α ′ ) corrections on the worldsheet. What is absolutely clear is that in the context of holography at large N , where both string genus and α ′ corrections are suppressed, Non-Abelian T-duality can be a powerful solution generating technique as advocated first in [3][4][5][6] (see [7] for a review and further references) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the correction to the background fields can be cast in a relatively simple form, giving hope that the result can be extended to all orders in the deformation parameter and perhaps higher orders in α ′ .Since the homogeneous YB deformations can be constructed using NATD, our results indicate that also NATD should preserve conformality at two loops, and possibly all orders in α ′ . Another piece of evidence for this comes from the recent analysis of renormalizability of deformed sigma models with two-dimensional target space in [28], and very recently [29]. Some of the deformations considered have a limit where they reduce to NATD and it was found that the models behave nicely beyond lowest order in α ′ suggesting that things should work out to all orders in α ′ .For YB deformations of TsT-type we can also exploit another method to obtain explicit α ′ -corrections and to promote those backgrounds to two-loop solutions.…”
mentioning
confidence: 99%